Assessment of Sensory Block During Labor Epidural Analgesia: A Prospective Cohort Study to Determine the Influence of the Direction of Testing. Issue 1 (22nd March 2023) - De Souza Soares, E.C.; Balki, M.; Downey, K.; Ye, X.Y.; Carvalho, J.C.A.
Abstract : ( Can J Anesth/J Can Anesth . 2022;69:750–755) Sensory block, or a decreased sensitivity to sensory stimuli, occurs with epidural anesthesia during labor. Assessing the degree of sensory block is important both for clinical practice and for patient safety, yet the assessment procedure is not standardized. A variety of stimuli have been used, as well as a variety of endpoints for determining the level of sensory block. This lack of standardization causes not only a difference in the way independent clinicians determine sensory block, it can also result in inconsistent description of these levels for the same patient, as well as issues with replication of studies and implementation of clinical practice.